A Review of the Asphalt Mixtures Containing Recycled Solid Waste Materials (Journal of Engineering, 2022)
Landfill and incineration are the most common and widely used methods to dispose of solid wastes; both of these techniques are considered the main sources of pollution in the world due to the harmful toxic emissions that are considered an environmental problem. Because of the large areas used by landfills, they are not always considered an economical method. With the increase in the production of solid materials, solid wastes increase the pressure on incinerators and landfills, making the environmental pollution hazard more serious. Instead, these waste materials can be used in some other applications. One of the most important of these applications is asphalt pavements, which are the most used types of pavements in the world. This study is to review the properties and performance of asphalt mixtures that contain different ratios of recycled PET and glass waste as a filler, partial replacement of fine aggregate, and binder modifier. These mixtures showed positive and accepted results for standard specifications.